Digital Skills and Transformational Leadership as Drivers of Business Performance in SMEs - Asraf, Asraf; Roslan, Astil Harli; Bagea, Arfin (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the influence of Digital Skills and Transformational Leadership on Business Performance, as well as test the role of Transformational Leadership as a moderation variable in the relationship between Digital Skills and Business Performance. The study used a quantitative approach with an explanatory design, involving 150 owners of Small and Medium-sized Enterprises (SMEs) in Kendari City as respondents. Data collection was carried out through a survey using a closed questionnaire with a five-point Likert scale. Data analysis was carried out using the Structural Equation Modeling method based on Partial Least Squares (SEM-PLS) to test the direct relationship and moderation effect between variables. The results of the study show that Digital Skills have a positive and significant effect on Business Performance, which shows that digital skills are an important factor in increasing operational effectiveness and business competitiveness. Transformational Leadership has also been proven to have a positive and significant influence on Business Performance, even with a stronger contribution in driving business performance. In addition, Transformational Leadership acts as a moderation variable that strengthens the relationship between Digital Skills and Business Performance. These findings confirm the importance of synergy between digital capabilities and transformational leadership in improving business performance. This research provides the implication that digital skills development and transformational leadership need to be a strategic priority for SMEs in dealing with business dynamics in the digital era.